2020
DOI: 10.1007/s13280-020-01361-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus retention, erosion protection and farmers’ perceptions of riparian buffer zones with grass and natural vegetation: Case studies from South-Eastern Norway

Abstract: Phosphorus retention and bank erosion was investigated in two types of buffer zones in cereal fields in Norway: zones used for grass production and zones with natural vegetation. Farmers’ views on the two types of buffer zones were collected through questionnaires and in-depth interviews. Our results indicate that the grassed buffer zones had higher levels of plant-available phosphorus and lower infiltration rates than the natural ones. Bank erosion was higher in zones with grass production than those with tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Environmental goals determine the amount of mitigation measures needed, and as we move towards a future with both changed climate and land use, it is likely that a new generation of mitigation measures must be developed. This means that there is a need to improve the targeting, precision, cost-effect and cost-benefits of the measures, while at the same time enhancing multiple functions and reducing negative side effects (Blankenberg and Skarbøvik 2020;Carstensen et al 2020;Djodjic et al 2020;Hashemi and Kronvang 2020). Increased conflicts between mitigation measures and production of biomass are not unlikely in the future bioeconomy and this calls for studies that minimise the land needed for mitigation measures without compromising the ecological needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental goals determine the amount of mitigation measures needed, and as we move towards a future with both changed climate and land use, it is likely that a new generation of mitigation measures must be developed. This means that there is a need to improve the targeting, precision, cost-effect and cost-benefits of the measures, while at the same time enhancing multiple functions and reducing negative side effects (Blankenberg and Skarbøvik 2020;Carstensen et al 2020;Djodjic et al 2020;Hashemi and Kronvang 2020). Increased conflicts between mitigation measures and production of biomass are not unlikely in the future bioeconomy and this calls for studies that minimise the land needed for mitigation measures without compromising the ecological needs.…”
Section: Discussionmentioning
confidence: 99%
“…The need for measures that not only address single issues was also emphasised by Blankenberg and Skarbøvik (2020), who studied in a more integrated manner the functioning of riparian buffer zones in South-East Norway and their importance in the future bioeconomy. They found that buffer zones intended for grass production in general had fewer positive effects (nutrient retention, bank erosion, biodiversity) than the ones with natural vegetation.…”
Section: Run Catchment Models and Assess Environmental Mitigation Impmentioning
confidence: 99%
“…Globally, several studies evaluated the RBZs' effectiveness on controlling the sediments and nutrients and reported that the effectiveness varied across geographic regions [4,[8][9][10][11], from 20% to 100% of nitrogen [9], 27% to 97% total phosphorous [12], and 84% to 90% sediment trapping effectiveness [13,14] across European countries to the southeastern United States. Recently, Ghimire et al [14] performed a sensitivity assessment of RBZ design strategies to stream water quality in three southeastern U.S. watersheds and reported comparable reductions of sediment (61% to 96%), total nitrogen (34% to 55%), and total phosphorous (9% to 48%) as compared to the stream water quality without the RBZ applications.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, several studies addressed the riparian buffers' impacts on sediment and nutrient removal effectiveness [6,7,11,14,15]. Others studied riparian ecosystems, nutrient biogeochemical and hydrological processing, riparian buffer function, and modeling techniques [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Others studied riparian ecosystems, nutrient biogeochemical and hydrological processing, riparian buffer function, and modeling techniques [16][17][18][19]. However, effectiveness varies with buffer design (i.e., varying buffer vegetation and width), site-specific factors, such as buffer management, agricultural practices (crop rotations and fertilization), pollutant properties, biological processes, and the condition of riparian areas (hydrology, vegetation, and geomorphology) [9,12,15,20,21]. While some literature indicated that narrow, continuous buffers were more effective than intermittent, wide buffers, others found that narrow buffers contributed nitrogen to riparian zones [7,9,12,14].…”
Section: Introductionmentioning
confidence: 99%